The Correlation between Verbal and Physical Abuse on Training Motivation and Mental Toughness of Volleyball Athletes in Semarang City - Lisa Andani Putri; Rahardjo, Hermawan Pamot; Setyawati, Heny (Journal of Physical Education and Sports, 2025)
Nowadays, many coaches do verbal and physical abuse to their athletes because the coaches consider it as a normal action and even included in the training program and able to discipline athletes. This study aimed to identify the correlation berween verbal and physical abuse on training motivation and mental toughness of volleyball athletes. This study used cross-sectional correlation with dual paradigm design. The sample used in this study are 155 female volleyball athletes from Semarang City. The research instrument to measure data used: 1) Korean Version of Verbal Abuse Questionnaire (K-VAQ), 2) Interpersonal Violence in Sport questionnaire (IViS), 3) Training Motivation Scale, and 4) Mental Toughness Scale. The result showed that there was a significant correlation between verbal abuse on training motivation (p = 0,00), physical abuse on training motivation (p = 0,00), physical abuse on mental toughness (p = 0,01), verbal and physical abuse on training motivation (p = 0,00), and verbal and physical abuse on mental toughness (p = 0,04). No significant correlation was found between verbal abuse on mental toughness (p = 0,07). The study concluded that there is a correlation between verbal and physical abuse and training motivation and mental toughness.